Características agronômicas e valor alimentício das silagens de milho e soja em monocultivo e consorciadas, avaliadas em ovinos em terminação - Bolson, Dheyme Cristina (2018)
The objective of this study was to evaluate the productive characteristics of corn and soybean in monoculture and intercropped and the silage quality of these crops, in relation to the fermentation profile, aerobic stability, performance and meat quality of finished lambs. For all evaluations, the 2B877PW maize hybrid and RR2 Pro® soybean variety were used. For the productive evaluations, a completely randomized design was used, considering 5 replications and 3 treatments: corn in monoculture, soybean in monoculture and corn and soybean intercropped. The planting design was realized in single lines with 90 and 45 cm of spacing for corn and soybean in monoculture, respectively. In the intercrop, soybean was sowed between of the maize lines and represented 15% in natural matter of the mixture. After harvesting the crops, prioritizing the corn ensilage point (½ of the milk line), the forages were ensiled in 200 L experimental silos and stored for 90 days in a completely randomized design with 5 replicates per treatments denominated: maize silage in monoculture (MS), soybean silage in monoculture (SS) and maize silage and soybean intercropped (MSS). To evaluate the productive performance, eight male lambs per treatment were used, totaling 24 animals, with a mean weight of 23 kg (± 3.50). The evaluation period was 70 days (20 d for adaptation and 50 d for data collection) until the animals reached an average weight of 35 kg (± 2.20). The animals were distributed in blocks considering the initial body weight as a covariate in a randomized design. After the slaughter samples of Longissimus dorsi were collected for evaluations of meat characteristics, such as subcutaneous fat thickness, loin eye area, pH, texture, marbling, meat and fat color, cooking and drip losses, lipids antioxidant activity, lipid oxidation and fatty acid profile. For the productivity evaluations, the maize-soybean intercrop presented a reduction in forage (-10.4 ton.ha-1) and grain yield (-2.6 ton.ha-1). The percentage of grain in relation to the DM produced reduced about 4.8%. The CP content of the MSS (10.3%) was higher than MS (7.35%), without affecting the fibrous constituents, IVDMD, fermentation and fermentative losses. The low proportion of soybean in the mixture was not sufficient to improve the aerobic stability of the intercrop silage (72 h). Due to the characteristics of the legume, the SS did not present a chemical composition and fermentation profile suitable for material preservation, with low DM (24.2%), high pH (5.26), high proportions of N-NH3 (9.63%), acetic acid (4.31%) and butyric acid (8.75%). The diet with MS promoted higher animal performance, resulting from higher nutrient intake (1097 g.day-1) and digestibility (69.6%), compared to the SS diet (967 g.day-1 and 62.5%, respectively). The diet with MSS presented similar results to the one with MS. SS is not recommended as the sole source of bulky for animals in intensive production systems. The meat quality of the lambs fed with MS diet showed improvement in all evaluated characteristics. The SS diet did not promote changes in meat characteristics, so it is necessary to evaluate the feasibility of reducing costs for inclusion in the diet and the real benefit of the intercropping technology. In general, the production of grass and legume silages in order to increase the protein content of the crop is questionable. In addition, for intercropping, it is difficult to relate the harvesting point of both crops to benefit silage. Regarding the productive performance, the maize and soybean consortium presented results similar to corn in monoculture. However, it is necessary to assess whether the inclusion of soybeans would ensure the reduction of protein concentrates and minimize production costs